Can federal policy help overcome systemically reinforced racial inequities in social determinants of health? An observational study of Georgia and neighboring U.S. states - Eric Napierala; Bill Rencher; Lori Solomon; Chris Parker (BMC Public Health, 2024)
Abstract Background Despite increasing attention to racial inequities in social determinants of health and health outcomes, less attention has been focused on how structural barriers — embedded in programs and codified in laws — shape opportunities to achieve health. Methods To better understand how U.S. federal policies targets structural barriers to opportunity and health at the population level, we conducted a legal review to identify landmark pieces of federal policy that held potential to impact key social determinants of health. Then, using publicly available data for Georgia and five neighboring U.S. states (Alabama, Florida, North Carolina, South Carolina, and Tennessee), we conducted an observational case study to examine recent trends for access to health care, housing, and education because they were each associated with comprehensive federal legislation meant to alleviate inequities resulting from long-standing structural barriers and were each identified by Healthy People 2030 as key social determinants of health. Results From 2010 to 2021, population-level improvements were seen in health insurance rates, mortgage and rental burden, and educational attainment, with improvements seen for both Black and White populations in Georgia, regionally in the Southeast region, and nationally in the United States. However, seemingly meaningful gaps between the Black and White populations across social determinants of health have not been eliminated at any geographical level. Conclusions This analysis adds to a growing body of evidence that historically racialized social structures hamper Black populations’ opportunities to build wealth, gain a quality education, own a home in a neighborhood of opportunity, and access health care, compared to their White peers. Given that the root causes of health disparities and inequities lie at the intersection of health, health care, economics, education, and other social systems, a multisectoral approach to policy is needed to address these systemic issues. While federal laws do provide momentum for proximal benefits for social change, in modern federalism they alone are insufficient to address needed local system change and nonlegal policy interventions, implemented at the local programmatic level, may serve as complementary mechanism to address the lingering effects of barriers to equal opportunity.